Private Debt and GDP: A Short-Run Perspective - Gianluca Cafiso (Center for Economic Studies and ifo Institute (CESifo), 2016)
Mainstream economic research regards private debt as a determinant of GDP growth in the longrun. Levine (2005) surveys in details this branch of literature and explains the channels by which debt fuels growth. In this paper we switch the focus from the long to the short-run and study whether private debt has a significant impact on GDP growth in the short-run too. Our aim is to understand whether policy measures aimed to reduce the cost of private debt may favor a quick increase of the economic activity.
Keywords: O11; O16; O51; O52; E44; 330; private debt; GDP; short-run; VAR